THE INFLUENCE OF K-POP EXPOSURE THROUGH SOCIAL MEDIA ON ENGLISH VOCABULARY MASTERY AMONG SENIOR HIGH SCHOOL STUDENTS - Andira Putri, Auliya; Anwar Korompot, Chairil; Rayhana Sofyan, Ryan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The growing popularity of K-Pop among Indonesian adolescents has opened new opportunities for informal English exposure through social media platforms such as Instagram, TikTok, YouTube, and Weverse. Students frequently encounter English vocabulary through song lyrics, subtitles, captions, comments, and online interactions embedded in K-Pop content. This study examined the influence of K-Pop exposure through social media on senior high school students' English vocabulary mastery. Using a quantitative correlational design, the study involved 50 students of SMA Negeri 3 Bulukumba selected through purposive sampling. Data were collected using a K-Pop Exposure Questionnaire and a Vocabulary Mastery Test measuring word meaning, word form, and lexical meaning, and were analyzed through descriptive statistics, Pearson Product Moment Correlation, and Simple Linear Regression with the assistance of IBM SPSS. Prior to hypothesis testing, the data were confirmed to satisfy the assumptions of normality, linearity, homoscedasticity, and independence of errors. The results showed a strong, statistically significant positive correlation between K-Pop exposure and vocabulary mastery (r = 0.671, p < 0.001), and regression analysis indicated that K-Pop exposure accounted for 45.1% of the variance in students' vocabulary mastery (R² = 0.451, F = 39.388, p < 0.001), with the regression equation Y = 1.741 + 0.180X. These findings demonstrate that authentic and repeated English input embedded in K-Pop content can meaningfully support incidental vocabulary development, positioning social media as a valuable informal learning resource that complements formal English instruction.